Morbid obesity leads to increased skin autofluorescence independent of metabolic syndrome components - APAYDIN, TUĞÇE; YAVUZ, DİLEK (My University, 2022)
Background/aim: Obesity, diabetes mellitus, and metabolic syndrome (MetS) are associated with increased accumulated skin advanced glycation end products. We aimed to evaluate the association of MetS components with skin autofluorescence (SAF) in patients with morbid obesity. Material and methods: Eight hundred and one patients with morbid obesity and 94 age-matched controls with normal body mass index (BMI) and normal glucose metabolism were included. Advanced glycation end products (AGEs) were measured using SAF in the forearm, with an AGE reader. Results: The prevalence of MetS in patients with morbid obesity was 65.5% (n = 525). Type 2 diabetes mellitus (type 2 DM) and hypertension were present in 40.9% (n = 328) and 43.7% (n = 357). Patients with morbid obesity and those with MetS had higher SAF measurements compared with the control group, 1.85 ± 0.44 arbitrary unit (AU) and 1.86 ± 0.43 AU vs. 1.72 ± 0.30 AU, respectively (p = 0.016). There was no difference in SAF levels between patients with and without MetS. SAF measurements of patients without MetS were not statistically different from the control group (p = 0.076). Patients with five MetS criteria had higher SAF measurements compared with patients with fewer MetS components (p = 0.019). There was no difference in SAF levels between patients with type 2 DM, impaired glucose metabolism, and patients with normal glucose metabolism (p = 0.513). Conclusion: Although MetS and type 2 DM are known as factors related to increased SAF levels, obesity can cause elevated SAF measurements in different ways independent of concomitant comorbid diseases. Larger studies with longer follow-ups are needed to enlighten the underlying mechanism.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Advanced glycation end products; metabolic syndrome; morbid obesity; skin autofluorescence; GLYCATION END-PRODUCTS; BARIATRIC SURGERY; ENDOTHELIAL DYSFUNCTION; NONINVASIVE MARKER; ENDPRODUCTS; MORTALITY; RISK; Advanced glycation end products; metabolic syndrome; morbid obesity; skin autofluorescence